COGNITIVE FUNCTION OF METAPHORS IN LUKAS VERSES OF THE BIBLE - Ina Swari Jabat; Busmin Gurning; Didik Santoso (LINGUISTIK TERAPAN, 2018)
This research is aimed to explore the cognitive function of metaphor in Jesus teaching in Lukas verses in parables. The research applies the Conceptual Metaphor Theory. The data is taken from fourteen verses of Lukas chapter 12 verse 35 to 48. The data analysis is applying the Creswell data analysis Hierarchal Data Analysis Technique. The data shows cognitive functions of Jesus’ Teachings to Bible’s readers. The data analysis revealed, there are 36 metaphors used. These metaphors are classified into categories of structural metaphors, ontological metaphors and orientational metaphors. The data show that Lukas chapter 12 verse 35 to 48 use the three cognitive function of metaphors, structural function, ontological function and orientational function. There is also with one additional function that there is metaphor formed as structural function but functioned as ontological function. And then, the metaphors are motivated by the similarity of experience between the metaphor and the back ground of the verses. Keywords: Conceptual Metaphors, Lukas Verses, Cognitive Function